2021
DOI: 10.1161/circulationaha.121.056208
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Cardiac Troponin Elevations: From Underlying Mechanisms to Clinical Relevance

Abstract: Serological assessment of cardiac troponins (cTn) is the gold standard to assess myocardial injury in clinical practice. A greater magnitude of acutely or chronically elevated cTn concentrations is associated with lower event-free survival in patients and the general population. Exercise training is known to improve cardiovascular function and promote longevity, but exercise can produce an acute rise in cTn concentrations, which may exceed the upper reference limit in a substantial number of individuals. Wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 127 publications
(198 reference statements)
3
65
1
6
Order By: Relevance
“…The magnitude of exercise-induced cTn elevations, timing of peak concentrations and the prevalence of post-exercise hs-cTnT concentrations above the upper reference limit align with findings from previous publications. 2 , 5 These observations show that the intensity and duration of our exercise protocol sufficiently stressed the heart to cause significant increases in hs-cTnT concentrations.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The magnitude of exercise-induced cTn elevations, timing of peak concentrations and the prevalence of post-exercise hs-cTnT concentrations above the upper reference limit align with findings from previous publications. 2 , 5 These observations show that the intensity and duration of our exercise protocol sufficiently stressed the heart to cause significant increases in hs-cTnT concentrations.…”
mentioning
confidence: 57%
“… 1 Stressing the heart with exercise potentially increases sensitivity of detecting myocardial injury, as evidenced by exercise-induced cTn elevations. 2 Hence, exercise might reveal myocardial vulnerability, which could remain unrecognized under resting conditions. Therefore, we assessed exercise-induced high-sensitivity cardiac troponin T (hs-cTnT) release in middle-aged athletes recovered from COVID-19 and compared their response to matched controls.…”
mentioning
confidence: 99%
“…Thus, W. Cheng et al reported that apoptosis of CMC increases with stretching of the myocardial walls ( Cheng et al, 1995 ). This allows us to consider many physiological and pathological conditions that cause stretching of the myocardial walls as possible inducers of apoptosis and thus can, to some extent, explain the increased serum levels in patients after prolonged and intense physical exertion or having AH, PE, COPD and a number of other pathologies ( Cheng et al, 1995 ; Park et al, 2017 ; Gherasim, 2019 ; Aengevaeren et al, 2021 ).…”
Section: Release Of Cardiospecific Tns As a Results Of Apoptosis Of Cmcmentioning
confidence: 99%
“…The time course of elevated cTn levels after prolonged exercise (peak values between 2 and 6 h after exercise) is different to that caused by myocardial infarction (peak values between 10 and 12 h after an ST segment-elevation acute myocardial infarction) [21]. The early releasable cTn pool is considered the primary origin of release.…”
Section: Myocardial and Renal Injuries Followingmentioning
confidence: 98%
“…The early releasable cTn pool is considered the primary origin of release. Conversely, increased cTn levels caused by irreversible myocyte injury with apoptosis and/or necrosis stem from cTn complexes, which are structurally bound to the actin filament and represent the majority of cTn [21,22].…”
Section: Myocardial and Renal Injuries Followingmentioning
confidence: 99%